Assessing and responding to anxiety and panic in the Emergency Department. (December 2019) - Derrick, Kate; Green, Tim; Wand, Timothy
Abstract: Anxiety and panic symptoms are widespread in the general population. The physical manifestations of anxiety and panic commonly account for people presenting to Emergency Departments (EDs). It is therefore important for ED clinicians to be informed of the numerous causes of anxiety and panic and equipped to respond effectively. This paper describes the underlying pathophysiology of the physical symptoms of anxiety and panic and differential diagnoses to consider. Organic conditions that are associated with symptoms of anxiety and panic are highlighted. Brief interventions are tabled for ED clinicians to use when explaining symptoms, and to promote individual self-management.